2014
DOI: 10.1093/cid/ciu219
|View full text |Cite
|
Sign up to set email alerts
|

A Phase 3 Randomized Double-Blind Comparison of Ceftobiprole Medocaril Versus Ceftazidime Plus Linezolid for the Treatment of Hospital-Acquired Pneumonia

Abstract: Ceftobiprole is a safe and effective bactericidal antibiotic for the empiric treatment of HAP (excluding VAP). Further investigations are needed before recommending the use of ceftobiprole in VAP patients. Clinical Trials Registration. NCT00210964, NCT00229008.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
168
1
7

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 192 publications
(190 citation statements)
references
References 30 publications
14
168
1
7
Order By: Relevance
“…In 80% of cases the diseases severity scale (PORT) was mild to moderate ( III in a scale of I-V) and the cure rate was similar in both arms (86% versus 87%, 95% CI of the difference: À6.9 to 5.3). On the other hand, a double blind RCT in patients with nosocomial pneumonia with an overall mortality rate of 19%, showed that ceftobiprole was less effective than the combination of ceftazidime 2 g every 8 h plus linezolid 600 mg every 12 h (cure rates in clinically evaluable population, 69.3% versus 71.3%, difference: À2%, 95% CI: À10 to 6.1) [36 ]. All the difference was due to the worse results obtained in the subgroup of patients with ventilator-associated pneumonia (VAP) where the cure rates in clinically evaluable population were 37.7% versus 55.9% (difference: À18.2%, 95% CI: À36.4 to À.0), respectively.…”
Section: Ceftobiprolementioning
confidence: 99%
“…In 80% of cases the diseases severity scale (PORT) was mild to moderate ( III in a scale of I-V) and the cure rate was similar in both arms (86% versus 87%, 95% CI of the difference: À6.9 to 5.3). On the other hand, a double blind RCT in patients with nosocomial pneumonia with an overall mortality rate of 19%, showed that ceftobiprole was less effective than the combination of ceftazidime 2 g every 8 h plus linezolid 600 mg every 12 h (cure rates in clinically evaluable population, 69.3% versus 71.3%, difference: À2%, 95% CI: À10 to 6.1) [36 ]. All the difference was due to the worse results obtained in the subgroup of patients with ventilator-associated pneumonia (VAP) where the cure rates in clinically evaluable population were 37.7% versus 55.9% (difference: À18.2%, 95% CI: À36.4 to À.0), respectively.…”
Section: Ceftobiprolementioning
confidence: 99%
“…Its bactericidal activity also acts against Gram (+) bacteria, including resistant S. pneumoniae, MRSA and Enterococcus faecalis, but not against Enterococcus faecium. Ceftobiprole was shown to be noninferior to ceftazidime plus linezolid for the treatment of HAP in a phase III RCT (34), with clinical cure rates were 49.9% comparing to 52.8% for ceftobiprole and ceftazidime /linezolid, respectively. But, the clinical cure rate in the VAP population favored the linezolid/ ceftazidime arm over the ceftobiprole arm, 56.7% versus 38.5%, respectively (p < 0.05).…”
Section: Ceftobiprolementioning
confidence: 99%
“…Ceftobiprole (3-mal 500 mg) wurde in einer im Jahr 2014 publizierten randomisierten kontrollierten Studie gegen die Kombination von Ceftazidim (3-mal 2 g) und Linezolid (2-mal 600 mg) getestet [42]. In die Studie wurden 781 Patienten eingeschlossen, davon 210 mit einer VAP.…”
Section: Weitere Therapieoptionenunclassified